Dissociation between cognitive and affective empathy in youth with Asperger Syndrome - Rueda-Gallego, Pilar; Fernández-Berrocal, Pablo; Baron-Cohen, Simon (Taylor & Francis, 2015)
Autism spectrum conditions, among them Asperger Syndrome (AS), are generally described as entailing deficits in “cognitive empathy” or “theory of mind”. People with AS tend to have difficulties recognizing emotions, although the extent of these difficulties is still unclear. This study aimed to assess empathic profile in youth with AS (N ¼ 38) and controls matched on age, sex and IQ. The study aimed to test if a dissociation between cognitive and affective empathy exists in AS. The study also aimed to explore emotion recognition in people with AS, and how it relates to emotional valence (positive, negative, and neutral emotions). The AS group scored lower than controls on cognitive empathy but scored within the average range on affective empathy. A deficit in emotion recognition was found in the AS group for positive emotions. These results confirm earlier findings in cognitive empathy and provide new insight about emotion recognition abilities in this population.
Keywords: Asperger, Síndrome de; asperger syndrome; empathy; emotion recognition; theory of mind; eyes test